"That Must Have Been Uncanny!” Experiences of Invisible Others in Contemporary Finland - Andell Kia (De Gruyter Poland Sp. z o.o., 2025)
This article* examines experiences of invisible others considered uncanny in the context of secularity in contemporary Finland. Drawing from experience-centred theories of religion and spiritual belief by Ann Taves and David Hufford, the article analyses how uncanny experiences are differentiated from other kinds of experience and how they are justified as real in first-person narratives written by Finnish experiencers. The empirical analysis distinguishes four characterisations of experience the authors consider uncanny, which also serve to convince them of the realness of their experience. By conversating these findings with studies of experiences deemed religious or supernatural, the article seeks to reinforce dialogue with research on similar experiences that people rather consider in scientific and everyday terms. The article then suggests a framework for cross-secular enquiry that would allow scholars in different fields to address differences in how secularity manifests in different locations. Such a methodological framework may create possibilities to juxtapose and compare similar kinds of experience that people may or may not consider supernatural in different secular societies.